PELATIHAN EKONOMI KREATIF BAGI MASYARAKAT KORBAN BENCANA BANJIR BANDANG DESA LAMAWOLO LEMBATA - Gerardus Tukan; Anggelinus Nadut (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Lamawolo village in Ile Ape Timur sub-district, in Lembata district, was one of the villages that was affected by the landslide that occurred on April 5, 2021. Residents of the entire village, totaling 303 people and generally working as field farmers, were evacuated to SMPN 1 Nubatukan, Lewoleba city. While in the refugee camps, they do not carry out life activities or professions as they do in their hometowns. This situation causes boredom, psychological pressure and has the potential to cause mental disorders. Responding to these conditions, this activity was carried out with the aim of being one of the trauma healing methods. The method used was process skills. The types of training carried out were processing coconuts into VCO, various types of handicrafts, processing corn into chips, and making cassava chips. The activity was carried out for 3 days, from 26 to 29 April 2021. The participants involved in the activity were 26 people consisting of teenagers and adults. The results of the activities obtained are the production of VCO oil, corn chips and handicrafts from coconut shells. The participants were actively involved and enthusiastic about participating in the activities. Participants stated that this activity has helped overcome boredom, forget the trauma of the disaster and have the enthusiasm to start a new life after the disaster.